STRATEGI PENGENDALIAN TUBERKULOSIS DI PUSKESMAS PEKANBARU KOTA, TENAYAN RAYA DAN SIMPANG TIGA KOTA PEKANBARU - Meimi Laillah; Ridwan Manda Putra; Suyanto Suyanto (Program Pascasarjana Universitas Riau, 2021)
Tuberculosis (TB) is a chronic infectious disease caused by the Mycobacterium tuberculosis (MTB) which affects the lungs and other organ., Indonesia is the third highest after India and China and Indonesia’s top ten causes of death in Indonesia. The purposeofthis study wastodeterminestrategycontrolof the TB Program in Pekanbaru City. Thisstudyisresearchwith SWOT analysisandsurveyanddirectinterviews in thefield,and the studyisgoing onJanuary-February 2021 at Pekanbaru City Primary Health Care, Tenayan Raya and Simpang Tiga PrimaryHealth Care.interview and survey with a total sampling method of 84 samples. The study’s resultsfrom the government policy involved that supporting the TB program in Pekanbaru cityisrespectable. At thesametime, fromthecommunity in thefield, there are stillpeoplewhodo not understand TB disease, forexample, theincidenceof TB disease, mode oftransmission, andthedurationoftreatmentandprevention. Suggested in controllingthe program TB disease, it is necessary to provide education and explanation to sufferers and the surrounding community